Development of a quality assurance process for the SoLid experiment - Abreu, Y; Amhis, Y; Ban, G; Beaumont, W; Binet, S; Bongrand, M; Boursette, D; Castle, B; Chanal, H; Clark, K; Coupé, B; Crochet, P; et al. (IOP Publishing, 2019)
The SoLid experiment has been designed to search for an oscillation pattern induced by a light sterile neutrino state, utilising the BR2 reactor of SCK⋅CEN, in Belgium. The detector leverages a new hybrid technology, utilising two distinct scintillators in a cubic array, creating a highly segmented detector volume. A combination of 5 cm cubic polyvinyltoluene cells, with 6LiF:ZnS(Ag) sheets on two faces of each cube, facilitate reconstruction of the neutrino signals. Whilst the high granularity provides a powerful toolset to discriminate backgrounds; by itself the segmentation also represents a challenge in terms of homogeneity and calibration, for a consistent detector response. The search for this light sterile neutrino implies a sensitivity to distortions of around Script O(10)% in the energy spectrum of reactor bar nue. Hence, a very good neutron detection efficiency, light yield and homogeneous detector response are critical for data validation. The minimal requirements for the SoLid physics program are a light yield and a neutron detection efficiency larger than 40 PA/MeV/cube and 50% respectively. In order to guarantee these minimal requirements, the collaboration developed a rigorous quality assurance process for all 12800 cubic cells of the detector. To carry out the quality assurance process, an automated calibration system called CALIPSO was designed and constructed. CALIPSO provides precise, automatic placement of radioactive sources in front of each cube of a given detector plane (16×16 cubes). A combination of 22Na, 252Cf and AmBe gamma and neutron sources were used by CALIPSO during the quality assurance process. Initially, the scanning identified defective components allowing for repair during initial construction of the SoLid detector. Secondly, a full analysis of the calibration data revealed initial estimations for the light yield of over 60 PA/MeV and neutron reconstruction efficiency of 68%, validating the SoLid physics requirements.